2019
DOI: 10.1101/636076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A large-scale resource for tissue-specific CRISPR mutagenesis inDrosophila

Abstract: Genetic screens are powerful tools for the functional annotation of genomes. In the context of multicellular organisms, interrogation of gene function is greatly facilitated by methods that allow spatial and temporal control of gene abrogation. Here, we describe a large-scale transgenic short guide (sg) RNA library for efficient CRISPR-based disruption of specific target genes in a constitutive or conditional manner. The library consists currently of more than 2600 plasmids and 1400 fly lines with a focus on t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Using an endogenously GFPtagged version to examine the developmental expression profile of dTzap protein in DCNs, we found expression starting at P30, followed by downregulation at P50 and very low levels of expression in DCN cells in adults (Figure 2A, A'-E,E'). Next, we confirmed the loss of medulla axons phenotype observed in the initial screen using two independent RNAi lines (#100127, #27849) and CRISPR/Cas9 approach 39 , by expressing a dTzap gRNA and Cas9 specifically in DCNs (Figure 2F-I). This phenotype was not degenerative, as we did not detect differences between M-DCN axons number in young and old flies in both control and dTzap-RNAi background (Supplementary Figure S2C).…”
Section: Cg7101/dtzap Downregulation Causes Dcns Medulla Innervation ...supporting
confidence: 64%
“…Using an endogenously GFPtagged version to examine the developmental expression profile of dTzap protein in DCNs, we found expression starting at P30, followed by downregulation at P50 and very low levels of expression in DCN cells in adults (Figure 2A, A'-E,E'). Next, we confirmed the loss of medulla axons phenotype observed in the initial screen using two independent RNAi lines (#100127, #27849) and CRISPR/Cas9 approach 39 , by expressing a dTzap gRNA and Cas9 specifically in DCNs (Figure 2F-I). This phenotype was not degenerative, as we did not detect differences between M-DCN axons number in young and old flies in both control and dTzap-RNAi background (Supplementary Figure S2C).…”
Section: Cg7101/dtzap Downregulation Causes Dcns Medulla Innervation ...supporting
confidence: 64%
“…This family of invertebrates (Insecta: Diptera: Drosophilidae) has continued to provide a successful avenue for innovative research partly because of the strong base of knowledge afforded by a single model species (i.e., Drosophila melanogaster), as well as because of the relatively simple brain (e.g., ∼100,000 neurons) (Scheffer, 2020). Here, CRISPR-Cas9 and other transgenic tools have already begun to be established for many closely related Drosophila species (Bono et al, 2015), including D. melanogaster (Port et al, 2020), D. simulans (Seeholzer et al, 2018) , D. yakuba and D. santomea (Ding et al, 2019) , D. pseudoobscura (Ramaekers et al, 2019) , D. subobscura (Tanaka et al, 2017) , D. sechellia (Auer et al, 2020) , D. suzukii (Karageorgi et al, 2017), as well as D. mojavensis (Khallaf et al, 2020). In addition, several other members of this fly genus are still in ongoing transgenic production in laboratories around the world.…”
Section: Introductionmentioning
confidence: 99%
“…mouse embryogenesis 45 . Also, studies have shown that CRISPR activity varies in different tissues 46 . This could bring challenges to adjusting speed in lineage recorders.…”
Section: Discussionmentioning
confidence: 99%